Modified Citrus Pectin Alleviates Cerebral Ischemia/Reperfusion Injury by Inhibiting NLRP3 Inflammasome Activation via TLR4/NF-ĸB Signaling Pathway in Microglia - Cui Y; Zhang NN; Wang D; Meng WH; Chen HS (Dove Medical Press, 2022)
Yu Cui,1,2 Nan-Nan Zhang,1 Dan Wang,1 Wei-Hong Meng,2 Hui-Sheng Chen1 1Department of Neurology, General Hospital of Northern Theater Command, Shenyang, People's Republic of China; 2Department of Life Science and Biopharmaceutics, Shenyang Pharmaceutical University, Shenyang, People's Republic of ChinaCorrespondence: Hui-Sheng Chen, Department of Neurology, General Hospital of Northern Theater Command, Shenyang, People's Republic of China, Email chszh@aliyun.com Wei-Hong Meng, Department of Life Science and Biopharmaceutics, Shenyang Pharmaceutical University, Shenyang, People's Republic of China, Email meng.weihong@qq.comBackground: Galectin-3 acts as a mediator of microglial inflammatory response following stroke injury. However, it remains unclear whether inhibiting galectin-3 protects against cerebral ischemia/reperfusion injury. We aimed to investigate the neuroprotective effects of modified citrus pectin (MCP, a galectin-3 blocker) in ischemic stroke and underlying mechanisms.Methods: The middle cerebral artery occlusion/reperfusion (MCAO/R) model in C57BL/6J mice and oxygen-glucose deprivation/reoxygenation (ODG/R) model in neuronal (HT-22) and microglial (BV-2) cells were utilized in the following experiments: 1) the neuroprotective effects of MCP with different concentrations were evaluated in vivo and in vitro through measuring neurological deficit scores, brain water content, infarction volume, cell viability, and cell apoptosis; 2) the mechanisms of its neuroprotection were explored in mice and microglial cells through detecting the expression of NLRP3 (NOD-like receptor 3) inflammasome-related proteins by immunofluorescence staining and Western blotting analyses.Results: Among the tested concentrations, 800 mg/kg/d MCP in mice and 4 g/L MCP in cells, respectively, showed in vivo and in vitro neuroprotective effects on all the tests, compared with vehicle group. First, MCP significantly reduced neurological deficit scores, brain water content and infarction volume, and alleviated cell injury in the cerebral cortex of MCAO/R model. Second, MCP increased cell viability and reduced cell apoptosis in the neuronal OGD/R model. Third, MCP blocked galectin-3 and decreased the expression of TLR4 (Toll-like receptor 4)/NF-κBp65 (nuclear factor kappa-B)/NLRP3/cleaved-caspase-1/IL-1β (interleukin-1β) in microglial cells.Conclusion: This is the first report that MCP exerts neuroprotective effects in ischemic stroke through blocking galectin-3, which may be mediated by inhibiting the activation of NLRP3 inflammasome via TLR4/NF-κB signaling pathway in microglia.Keywords: cerebral ischemia/reperfusion injury, microglia, galectin-3, modified citrus pectin, NLRP3 inflammasome